Publisher Correction: Persistent meanders and eddies lead to quasi‑steady Lagrangian transport patterns in a weak western boundary current - M. B. Gouveia (Nature Portfolio, 2021)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.